LEARNING IN HIGHER EDUCATION ORIENTED HIGH LEVEL THINKING ABILITY BY SETTING WEB-BASED DEVELOPMENT - Syamsul Arif (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
Higher Order Thinking Skills (HOTS) is a competency that must be achieved by students as stated in the 2013 curriculum. Indirectly, Unimed - LPTK which will create graduates to become teachers has a central role in realizing students who have such high-level thinking skills. Previously, when becoming a student at Unimed, high-level thinking skills of students had to be honed and improved continuously so that when becoming a teacher, Unimed graduates were able to train students to think high-level through HOTS-oriented questions. This study aims to: 1) Describe the relevance of the semester final exam questions compiled by the lecturer on the measurement of high-level thinking skills of Indonesian Language and Literature Department students, FBS Unimed, 2) Describe the relevance of teaching materials used by students to improve higher-order thinking skills, and 3) Developing a HOTS-oriented Indonesian language and literature learning assessment course module at Unimed FBS Language and Literature Department. This study uses a research and development (R & D) approach. The stages that will be carried out in this study include: defining, design, develop, and disseminate. The results showed that the learning planning tools made by the lecturers did not integrate the achievement of students' high-level thinking skills.